Shedding and immunogenicity of live attenuated influenza vaccine virus in subjects 5–49 years of age - Block, Stan L.; Yogev, Ram; Hayden, Frederick G.; Ambrose, Christopher S.; Zeng, Wen; Walker, Robert E. (Vaccine, 2008)
Live attenuated influenza vaccine (LAIV) is indicated for influenza prevention in persons 2–49 years of age. This study describes the incidence and duration of vaccine virus shedding and serum immune responses after receipt of LAIV. A single open-label dose of trivalent LAIV was administered intranasally to 344 subjects in 3 age cohorts: 5–8, 9–17, and 18–49 years of age. Shedding was determined by culture of nasal swabs (on days 1–7, daily; days 9–25, every other day; and day 28). Immunogenicity was measured as serum strain-specific hemagglutinin inhibition (HAI) titers (days 0, 28). Among subjects aged 5–8 years, 9–17 years, and 18–49 years, 44%, 27%, and 17% of subjects, respectively, shed vaccine virus after vaccination, and the mean number of positive samples per subject was 2.2, 1.8, and 1.5, respectively. Shedding occurred on days 1–11 postvaccination. Shedding incidence peaked on day 2, and maximum observed titers were highest on days 2–3 (<5, <4, and <3 log 10 TCID 50/mL, respectively, by age group). Despite positive cultures, all titers were <1 log 10 TCID 50/mL after days 10, 6, and 6, respectively, by age group. Shedding incidence was inversely correlated to age and baseline serum HAI titer. The seroresponse rate (4-fold rise in HAI) to at least 1 strain was 59% (68%, 64%, and 47%, respectively, by age group), and strain-specific rates were higher in baseline seronegative/serosusceptible subjects. Reactogenicity, most commonly runny nose, headache, and sore throat, was not associated with shedding or seroresponse. This is the first study to comprehensively evaluate nasal shedding of LAIV in individuals 5–49 years of age. Shedding was generally of short duration and at low titers. Study findings support the current recommendation of the Advisory Committee on Immunization Practices that LAIV recipients should only avoid contact with severely immunosuppressed persons (e.g., hematopoietic stem cell transplant recipients) for 7 days after vaccination.